An analytical framework for modelling intermetallic compound (IMC) formation and optimising bond strength in aluminium‐steel welds. Issue 3 (25th April 2019) - Grong, Øystein; Sandnes, Lise; Bergh, Tina; Vullum, Per Erik; Holmestad, Randi; Berto, Filippo
Abstract: In aluminium‐steel welding bonding occurs via intermetallic compound (IMC) formation. Therefore, the reaction layer thickness X is a key parameter controlling the bond strength. To enable prediction of the layer thickness in a real welding situation, a simple diffusion model has been developed. The model, which is isokinetic in nature, allows X to be calculated via the Scheil integral from knowledge of the weld thermal cycle. Its relevance to solid state butt welding of aluminium to steel is illustrated in two different case studies, representing best practice for friction stir welding (FSW) and hybrid metal extrusion and bonding (HYB), respectively.